Impact of a Renal Function–based Clinical Decision Support System in Reducing Inappropriate Prescribing: A Pre-post Intervention Study at a Vietnamese Tertiary Hospital - Vinh, Nguyen Thanh; Tuan, Dang Bao; Ngoc Minh, Do; Duy Thanh Huong, Nguyen; Quynh, Tran Thu; Cong Thuc, Nguyen; Thanh Hai, Nguyen; Phuong, Dong Thi Xuan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Background: Inappropriate prescribing in patients with renal impairment, including the use of contraindicated drugs and unadjusted doses, is a significant contributor to preventable adverse drug events. Clinical Decision Support Systems (CDSS) have been shown to reduce medication errors by providing real-time alerts during prescribing. This study aimed to evaluate the effectiveness of a renal-related prescribing alert system integrated into the hospital’s CDSS at a Vietnamese Tertiary Hospital. Methods: A pre–post interventional study was conducted over two three-month periods: before (June–August 2024) and after (December 2024–February 2025) the implementation of renal-related prescribing alerts in the CDSS. The intervention included (1) building a database of contraindicated and dose-adjusted drugs based on renal function, (2) integrating the database into the Hospital Information System (HIS), and (3) training prescribers on the alert function. Data were extracted from the electronic prescribing system and analyzed using Chi-square tests to compare pre- and post-intervention outcomes. Results: After CDSS implementation, the proportion of patients with at least one contraindicated drug decreased from 6.0% to 1.5%, and prescriptions containing at least one contraindicated drug decreased from 4.5% to 2.1% (p < 0.05). Likewise, the proportion of patients receiving at least one unadjusted dose decreased from 6.1% to 0.4%, and prescriptions requiring dose adjustment decreased from 4.0% to 0.8% (p < 0.05). Overall, inappropriate prescriptions related to renal function were reduced by 69.5% (from 1,307 to 399 cases). The most frequent inappropriate prescribed drugs after intervention were furosemide + spironolactone (28.6%), trimetazidine (22.3%), and amlodipine + valsartan + hydrochlorothiazide (15.8%). Conclusions: Integration of renal-related prescribing alerts into the CDSS significantly reduced inappropriate prescribing in patients with renal impairment. These findings highlight the potential of CDSS to enhance medication safety and prescribing quality, though continuous optimization and user engagement are needed to sustain long-term effectiveness.